DIRECT METHOD IMPLEMENTATION IN ARABIC LANGUAGE TEACHING: EXPERIMENTAL STUDY AT DARUSSALAM ISLAMIC BOARDING SCHOOL, MANTINGAN - Cecep Sobar Rochmat; Nabielah Khusaini; Mujib Abdurrahman; Marheni Br Maha (STIQ Amuntai, 2023)
The application of the direct method has become the identity of Arabic learning at Modern Islamic Boarding School Darussalam Gontor. For non-Arabic speakers, learning Arabic using Arabic as the learning destination language and without translating it into the mother tongue. The difficulty and lack of knowledge about Arabic surround the feelings of new students in learning it. The purpose of this research is to assess the efficacy of direct method implementation in Arabic language learning at Pondok Modern Darussalam Gontor Putri Campus 1. This research method uses quantitative experimental methods by holding a pre-test followed by direct method treatment to respondents and ending with a post-test trial. Population from the entire grade 1 study at Pondok Modern Darussalam Gontor 2023. The sampling technique uses random sampling with a total sample of 43 students. The results of this study aim to determine the effectiveness of the direct method in learning Arabic. Based on the result of the research conducted, there was an increase of 10,47% in post-test assessment after being given direct method treatment. There was an increase in the average pre-test from (6.95) to (8.42) in the post-test score. The results of the hypothesis test show that the significance value is 0.00 where if the value is below 0.05 then there is an effectiveness of the direct method in learning Arabic. On the other hand, Santriwati is very responsive and enthusiastic in learning Arabic using the direct method because some of them like (76.7%) to learn using the direct method than those who do not like (23.3%). From this, it can be concluded that the role of professional teachers armed with knowledge and practice greatly influences the success of the implementation of direct methods in teaching Arabic.